CLINICAL AND LABORATORY CHARACTERISTICS OF CHRONIC HEPATITIS C IN VIETNAM ON THE EXAMPLE OF HO CHI MINH CITY HEPATOLOGY CLINIC - D. A. Lioznov; N. H. Chung; S. L. Nikolaenko; T. B. Trung; F. T. Lan; N. Z. Phong (Журнал инфектологии, 2016)
Objectives. To provide clinical  and laboratory  characteristics of chronic  hepatitis C in Vietnam.Materials and  methods. A retrospective analysis of data about  1870 HCV  patients observed at Hepatology Clinic  in Ho Chi Minh  City, Vietnam from 2010 to 2015.Results. Among observed patients, HCV  genotype 1 is predominant (48.8%), genotype 6 was  registered in 29,7% of patients, and genotype 2 – 18,7%. Advanced fibrosis (F3) and cirrhosis (F4) were detected in 52% of patients. The rate of chronic  co-infection with  hepatitis B viruse  and  hepatitis C virus is at 6% of patients. Nearly  one-tenth of all observed HCV patients (9%)  were diagnosed with hepatocellular carcinoma. In the  group  of patients who completed the  full course  of treatment, non-responsers to therapy and  have  virologic  breakthrough, SVR-24  was registered at 73,7% and 75,1% of patients treated with  simple or pegylated interferon, respectively. Thus,  combination therapy with interferonalpha  and  ribavirin  for the  indigenous Vietnamese population has been showed relatively high efficiency.Conclusion. The  findings about  clinical  and  laboratory characteristics of patients with  chronic  hepatitis C, and  the effectiveness of antiviral therapy, have practical importance for preparation a long-term strategy for the  elimination of hepatitis C in Vietnam.